Implementation of the Insertion Sort Algorithm to Sort Positive Integers in Ascending Order Using Flowgorithm - Zulham Sitorus; Dhimas Prayogi; M. Azhari Rizko; Ade Guna Suteja; Muhammad Raihan Harahap (Journal of Information Technology, computer science and Electrical Engineering, 2024)
The advancement of information technology has had a significant impact on various fields, including education. One area that has been greatly influenced is the teaching of programming algorithms, where technology helps simplify the understanding of fundamental concepts, such as data sorting algorithms. This study focuses on the implementation of the Insertion Sort algorithm using the Flowgorithm application to facilitate the understanding of the data sorting process. Flowgorithm is a software tool that enables the creation of flowcharts to visually represent the steps of an algorithm, which can then be translated into programming languages. The Insertion Sort algorithm was chosen due to its simplicity and its effectiveness in sorting small datasets. This study covers the design and implementation of the algorithm using Flowgorithm, testing with positive integer data, and verifying the correctness of the sorting results through manual calculations. The test results show that the algorithm works correctly, producing the proper sequence from unsorted data. Additionally, the pseudocode generated from the Flowgorithm design can be translated into a programming language like Python. This research contributes to enhancing the understanding of algorithmic concepts, particularly sorting algorithms, by using Flowgorithm as an effective learning tool.